Identification of Systemic Drug Targets for Anti-cavernous Fibrosis in the Treatment of Erectile Dysfunction, Guided by Genome-Wide Mendelian Randomization - Zilong Chen; Quan Wang; Lianqin Zhang; Junfeng Qiu; Yangling Zeng; Hao Kuang; Chunxiu Chen; Zhiming Hong (American Journal of Men's Health)
The treatment of erectile dysfunction (ED) remains a significant challenge. Mendelian randomization (MR) is being increasingly utilized to identify novel therapeutic targets. In this study, we carried out a genome-wide MR analysis on druggable targets with the aim of pinpointing latent therapeutic alternatives for ED. We collected data on the druggable genes and filtered out those associated with blood eQTLs, then performed two-sample MR and colocalization analyses using ED genome-wide association data to screen genes significantly linked to the condition. In addition, we carried out phenome-wide studies, enrichment analysis, protein network modeling, drug prediction, and molecular docking. We screened 3,953 druggable genes from the DGIdb and 4,463 from a review. Following data integration, 74 potential druggable genes were found to potentially regulate corpus cavernosum fibrosis. MR analysis of eQTL data uncovered five drug targets (TGFBR2, ABCC6, ABCB4, EGF, and SMAD3) significantly associated with ED risk. Colocalization analysis suggested a shared causal variant between ED susceptibility and TGFBR2, with a posterior probability (PPH4) exceeding 80%. Drug predictions utilizing DSigDB identified nolone phenylpropionate, sorafenib, and NVP-TAE684 as significantly associated with TGFBR2. Finally, molecular docking indicated strong binding affinities between these candidate drugs and the protein encoded by TGFBR2 (Vina score < −50). Through MR and colocalization analyses, the present study identified five potential drug targets for ED, with TGFBR2 showing remarkable relevance in blood. These findings offer valuable insights and potential leads for the development of more effective ED therapies, which may also contribute to cutting down the expenses involved in drug development.